Gender Influence on Career Preferences in STEM: Unraveling Stereotypes and Fostering Diversity (Intitute of Computer Science (IOCS), 2022)
This research investigates the influential role of gender in shaping career preferences within the fields of science and technology (STEM). The study explores the extent to which gender-related factors impact career aspirations and the potential implications for gender diversity in STEM industries. Through a mixed-methods approach, combining qualitative interviews and quantitative surveys, data were collected from a diverse sample of individuals across various age groups and educational backgrounds. The research sought to identify patterns and trends in career preferences, particularly in relation to STEM disciplines. The findings of this study reveal significant disparities in career preferences between males and females. Gender stereotypes, societal expectations, and early educational experiences were identified as key determinants in driving these disparities. Women often reported feeling constrained by stereotypes associated with certain STEM fields, while men tended to gravitate toward traditionally